Haemodynamic Response to Induction and Intubation Using Propofol with Etomidate and Propofol with Phenylephrine – A Prospective Observational Study - Perumbally, Hawas Muhammed; Shafi PK, Mohammed; Isaac, Teeven Sam; Shiras P,; Shamila A, (Journal of Neonatal Surgery, 2025)
Background: Endotracheal intubation can cause significant hemodynamic fluctuations, necessitating the use of appropriate induction agents to ensure stability. Propofol is commonly used but may cause hypotension, while Etomidate offers better cardiovascular stability. Phenylephrine, a vasopressor, can counteract Propofol-induced hypotension. This study compares the hemodynamic effects of Propofol with Etomidate versus Propofol with Phenylephrine during induction and intubation.the objective of the study is to compare hemodynamic changes during induction and intubation using a combination of Propofol with Etomidate and Propofol with Phenylephrine by assessing blood pressure and heart rate variations. Methods: A prospective, randomized study was conducted on 50 patients undergoing elective surgery under general anesthesia with endotracheal intubation. Patients were randomly assigned to two groups: Group P received Propofol (2.5 mg/kg) with Phenylephrine (100 mcg), while Group E received Propofol (1.25 mg/kg) with Etomidate (0.15 mg/kg). Hemodynamic parameters, including systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and heart rate (HR), were recorded at baseline, immediately after induction, and at 1, 2, 3, and 5 minutes post-intubation. Additionally, postoperative adverse events such as nausea, vomiting, arrhythmias, and thrombophlebitis were monitored for 6 hours following surgery. Results: A statistically significant variation in SBP, DBP, and MAP was observed immediately after induction, with Group P demonstrating better hemodynamic stability and minimal blood pressure decline. No significant differences in HR were noted at any time point. Additionally, no statistically significant variations were observed between the two groups in hemodynamic parameters at 1, 2, 3, and 5 minutes post-intubation. Conclusion: The combination of Propofol with Phenylephrine resulted in better hemodynamic stability than Propofol with Etomidate, particularly in maintaining blood pressure post-induction. However, both regimens were comparable in terms of heart rate stability and postoperative complications.